2011
DOI: 10.4315/0362-028x.jfp-11-215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella on Raw Poultry at Retail Markets in China

Abstract: Data regarding Salmonella on raw poultry are very limited in China. The objective of this study was to determine the prevalence of Salmonella on raw poultry at the retail level in six provinces and two national cities in China. Whole chicken carcasses (n = 1,152) were collected from three types of retail markets (large, small, and wet). All samples were analyzed for the presence of Salmonella by using the U.S. Department of Agriculture, Food Safety Inspection Service method. Of 1,152 chicken samples, overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
6
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 20 publications
(21 reference statements)
10
56
6
2
Order By: Relevance
“…36 Butchery products were more contaminated with NTS (32%) than supermarket products (18%). This result, though contrary to the report by Yang et al 37 , was in agreement with the findings of Chaiba et al 35 and could be the result of better hygienic standards maintained in supermarkets than butcheries. Frozen products had a higher NTS recovery rate (10.4%) than fresh products (8.8%).…”
Section: Incidence Of Non-typhoidal Salmonella In Broiler Productscontrasting
confidence: 57%
“…36 Butchery products were more contaminated with NTS (32%) than supermarket products (18%). This result, though contrary to the report by Yang et al 37 , was in agreement with the findings of Chaiba et al 35 and could be the result of better hygienic standards maintained in supermarkets than butcheries. Frozen products had a higher NTS recovery rate (10.4%) than fresh products (8.8%).…”
Section: Incidence Of Non-typhoidal Salmonella In Broiler Productscontrasting
confidence: 57%
“…Interestingly, the overall incidence level of Salmonella (17%) from broilers was close to that (21.99%) reported earlier in Bangladesh [22]. Many studies showed different prevalence rates of Salmonella isolates in broilers worldwide: in Brazil, a low rate of 2.7% was reported [23], while in China, a high rate of 52.2% was reported [3]. These differences in prevalence rates may reflect considerable disparity in the sampling scheme, sample types, Salmonella detection protocol, and geographic location.…”
Section: Discussionmentioning
confidence: 78%
“…This is a cause for concern to public health authorities, owing to the associated risks of bacterial food poisoning [2]. Furthermore, poultry have always topped the list of foods associated with incidences of salmonellosis in many developing countries including India, Egypt, Brazil, and Zimbabwe [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Salmonella isolation rate for meat samples collected from the supermarket (37%) was similar to that of samples recovered from the wet market (45%). Salmonella isolates were recovered from 45 pork samples and 16 chicken samples at rates of 56% and 23%, respectively, which are recovery rates much higher than those of other countries but similar to those in a recent study from China (16)(17)(18). Since some of the samples contained two Salmonella isolates, a total of 112 Salmonella strains were collected for further characterization; among these 112 strains, 86 were isolated from pork and 26 were isolated from chicken.…”
mentioning
confidence: 86%